Multiculturalism rethought : interpretations, diemmas and new directions : essays in honour of Bhikhu Parekh - Uberoi, Varun, 1977-; Modood, Tariq; Parekh, Bhikhu C. (Edinburgh University Press, 2015)
A selection of the leading theorists of multiculturalism revisit aspects of Parekh's work both to underline its continuing importance and the ongoing vitality of multiculturalist theory.